Omacetaxine: a protein translation inhibitor for treatment of chronic myelogenous leukemia - Gandhi, Varsha (2014)
Chronic myelogenous leukemia (CML) is driven by the Bcr-Abl fusion protein which is a result of a (9;22) chromosomal translocation. Imatinib, dasatinib, and nilotinib (tyrosine kinase inhibitors, TKIs) have revolutionized how CML is treated. While the majority of patients respond to these kinase inhibitors, a subset become resistant to these therapeutics. Synribo (omacetaxine mepesuccinate) was recently FDA approved for Philadelphia-positive CML either in chronic or accelerated phase whose disease failed two prior TKIs. With omacetaxine 1.25 mg/m(2) twice daily for 14 days during induction and for 7 days during maintenance, a major cytogenetic response occurred in 20% of patients in chronic phase and major hematologic response in 27% of patients in accelerated phase. Laboratory investigations unraveled the mechanism of action and effectiveness of this agent. Bcr-Abl protein is intrinsically programmed to turn over with a short half-life which makes it susceptible to protein translation inhibitors. Omacetaxine (homoharringtonine) inhibits total protein biosynthesis by binding to A-site cleft of ribosomes. As a corollary to this action, there is a diminution of short-lived proteins such as Bcr-Abl followed by cell death. Approval of this first-in-class protein translation inhibitor opens up new avenues for its use in other diseases as well as mechanism-based combinations.